Synthesis and crystal structure of 1-(7-hydroxy-3-(4-hydroxy-3-nitrophenyl)-4-oxo-4H-chromen-8-yl)-N,N-dimethylmethanaminiumnitrate, C18H17N3O9 - Chen Hai-Lin; Yao Dong-Mei; Luo Ze-Ping; Wang Yan-Ping; Tang Yu-Mei (Zeitschrift für Kristallographie - New Crystal Structures)
C18H17N3O9, monoclinic, P21/c (no. 14), a = 15.3768(3) Å, b = 7.4510(2) Å, c = 15.6673(5) Å, β = 102.700(3)∘, V = 1751.13(8) Å3, Z = 4, Rgt(F) = 0.0405, wRref(F2) = 0.1157, T = 100 K.